MOTIVATION OF STUDENTS PLACED TO STAY IN PONDOK PESANTREN MIFTAHUL KHOIR DAGO BANDUNG - mustadim wahyudi (Universitas Pendidikan Indonesia, 2020)
This study aims to see and know the various motivations that make students choose to reside in Islamic boarding schools. The Islamic boarding school in question is the Miftahul Khoir Dago Bandung Islamic Boarding School which is also a place of research. Furthermore, students residing in Islamic boarding schools are referred to as Santri. This research uses a quantitative descriptive approach, using observation as a preliminary study, questionnaire distribution, and documentation for extracting and completing data. The subjects in this study were all students of i'dad class students with a total of 66 students, with details of 40 male students and 26 female students. Based on the results of data analysis obtained in the field, it is stated that the motivation of students to choose to live in a pesantren is caused by internal factors based on self-decisions showing a percentage of 78.38%, external factors based on parents' motivation of 75.68%, and factors needs that indicate an average percentage of 79.92%, consisting of (1) physiological needs, (2) security needs, (3) social needs, 4) self-esteem needs / rewards, and (5) self-actualization needs. So that it can be categorized very well, this shows that the results obtained are positive for students who choose to live in boarding schools.